Private investment, government expenditure and tax burden in Latin America - Brito-Gaona, Luis Felipe; Iglesias, Emma M. (Estudios de Economía, 2017)
This paper looks for empirical evidence to show if a very interventionist government stimulates or not private investment in Latin America. Using the same model as Caballero-Urdiales y López-Gallardo (2012), we extend their analysis from five Latin-American countries to all Latin America. The results from our estimated elasticities show evidence in support of three hypothesis: (1) that tax burden (taxes on income and consumption) has significant effects on privateinvestment; (2) that public investment has a crowding out effect with private investment; (3) and that in order to stimulate private investment, the government should have very little intervention.